2018
DOI: 10.1002/jcla.22423
|View full text |Cite
|
Sign up to set email alerts
|

The CDKN2A polymorphisms and the susceptibility of HBV‐related gestational diabetes mellitus

Abstract: In conclusion, the CDKN2A rs10811661 and rs564398 polymorphisms showed association with a greater risk of HBV-related GDM in a Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“… 52 Wang et al found that the ANRIL rs564398 polymorphism is associated with an increased risk of HBV-related gestational diabetes mellitus in a Chinese population. 53 Other studies have confirmed that the ANRIL rs564398 variant is significantly associated with myocardial infarction after multivariate adjustments for coronary artery disease. 54 However, the present study found that the ANRIL rs564398 variant allele was not related to susceptibility to recurrent miscarriage.…”
Section: Discussionmentioning
confidence: 94%
“… 52 Wang et al found that the ANRIL rs564398 polymorphism is associated with an increased risk of HBV-related gestational diabetes mellitus in a Chinese population. 53 Other studies have confirmed that the ANRIL rs564398 variant is significantly associated with myocardial infarction after multivariate adjustments for coronary artery disease. 54 However, the present study found that the ANRIL rs564398 variant allele was not related to susceptibility to recurrent miscarriage.…”
Section: Discussionmentioning
confidence: 94%
“…UGT1A4, CYP2A6, CSF2, INRS, GSTM1, and BMP6 had the lowest relevance score of 20.08, 20.03, 20.47, 20.02, 20.0, and 20.02, respectively. The list of genes/protein molecules regulated by the HBV and each chemical-induced hepatitis which is obtained from a peer review of the literature (along with references [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , ...…”
Section: Resultsmentioning
confidence: 99%